Semantic link of allusions and non-verbal communication in Ferdowsi's Shahnameh - Zahra Jamshidi; Seyyed Mohammad Arta (مطالعات زبانی و بلاغی)
Irony, as a literary element, brings to mind two external and internal meanings and leaves the reader'sIrony, as a literary element, brings to mind two external and internal meanings and leaves the reader's understanding in suspense and postpones his reception. From the point of view of aesthetics, because it creates images, it creates artistic beauty; Therefore, irony has a special place in literature, and poets have taken advantage of it in order to avoid direct and explicit expression, and they have presented their intention and objectivity in the form of this expression. Non-verbal communication and body language is also one of the manifestations of normal and everyday language, which is considered a helpful element; This means that non-verbal behavior can be used along with verbal communication, and with its help, one can convey one's intention to the audience better, more accurately and sometimes more effectively.Various reasons can be listed for the great influence of irony in words, one of which is the close connection of irony with non-verbal behaviors and the semantic connection and conceptual dependence of these two categories. In the present essay, the author investigated the ironies derived from the concept of non-verbal behaviors with a descriptive-analytical method and a case study of Ferdowsi's Shahnameh and came to the conclusion that a large part of the ironies was adapted from the concept of non-verbal behaviors and there are comprehensible semantic relationships between these two categories and understanding the semantic relationship between these two categories of literature and language leads to the discovery of a subtle relationship between literary language and ordinary language. Movement behaviors, facial behaviors, environment and physical appearance are respectively the most frequent behaviors from which allusions in the Shahnameh have been received.